Monochorionic-specific association between first-trimester serum ferritin and gestational diabetes in twin pregnancies: a retrospective cohort study - Ni, Yanyan; Bi, Yan; Xu, Xiaona; Hu, Yucheng; Ma, Jue; Wang, Yanlin (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have demonstrated that elevated serum ferritin (SF) levels in early pregnancy are significantly associated with the risk of developing gestational diabetes mellitus (GDM). However, these findings have primarily focused on singleton pregnancies, and evidence in twin pregnancies remains underexplored. This study aimed to explore the association between early-pregnancy SF levels and the risk of GDM in twin pregnancies, with a particular focus on different chorionicity types.MethodsWe conducted a retrospective cohort study involving 882 twin pregnancies delivered at our hospital between January 2019 and December 2021. The cohort included 700 dichorionic diamniotic (DCDA) and 182 monochorionic diamniotic (MCDA) pregnancies. Cases with gestational age at delivery less than 28 weeks, pre-existing diabetes, unknown GDM status, or mid-trimester fetal reduction in monochorionic-triamniotic (MCTA) pregnancies were excluded. GDM was diagnosed using a 75 g oral glucose tolerance test (OGTT) based on the IADPSG criteria. Serum ferritin (SF) levels were measured during the first prenatal visit in the first trimester. Logistic regression, linear correlation analyses and Receiver Operating Characteristic (ROC) curve were performed to assess associations between SF and GDM.ResultsIn MCDA pregnancies, women with GDM had significantly higher mean SF levels compared to those without GDM (101.68 ± 59.72 vs. 79.87 ± 53.11 μg/L, p<0.05). However, no significant difference was observed in DCDA pregnancies. In MCDA cases, SF levels >71.4 μg/L were independently associated with an increased risk of GDM (adjusted OR = 2.775, 95% CI: 1.191–6.466; p=0.018), with a significant trend across SF levels (p for trend = 0.012). Additionally, SF was positively correlated with fasting blood glucose in early pregnancy (r=0.17, p=0.025) and 1-hour OGTT glucose at 24–28 weeks (r=0.15, p=0.041) among MCDA pregnancies.ConclusionsElevated SF levels in early pregnancy are independently associated with a higher risk of GDM in MCDA twin pregnancies and may serve as a potential early biomarker for GDM prediction. In contrast, no significant association was found in DCDA pregnancies, indicating that the predictive value of SF may differ by chorionicity. Further studies are warranted to confirm these findings and investigate the underlying mechanisms.